URGENSI TUMBUH KEMBANG ANAK TERHADAP PEMBENTUKAN KARAKTER - Sholichah, Aas Siti (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
The phase of development of the child's age affects the formation of character. Age 0-4 years cognitive development reaches 50%, this age is called the golden age. Ages 4-8 years by 30% and ages 9-17 years 20%. What is seen, heard and learned will take root and shape the child's perception of life experienced. If a child of this age is raised with love, appreciation and empathy, then what is experienced will be engraved and rooted into character. But if what is seen, experienced and felt something painful and unsafe, it will form a character who is easily discouraged, unstable and stubborn. For that the role of the closest person, namely parents, contributes to shaping the character of the child.